High Utility Pattern Mining ï¿½ A Deep Review - Tale, AA; Wankhade, NR (International Journal of Computer Sciences and Engineering, 2025)
The mining high utility pattern is new development in area of data mining. Problem of mining utility pattern with itemset share framework is tricky one as no anti-monotonicity property with interesting measure. Former works on this problem employ a two-phase, candidate generation approach with one exception that is however inefficient and not scalable with large database. This paper reviews former implementation and strategies to mine out high utility pattern in details. We will look ahead some strategies of mining sequential pattern.